Phylogeny and biogeography of the lucanid beetles of the tribe Aesalini (Insecta, Coleoptera, Lucanidae), with special reference to the effect of Himalayan uplift as the vicariance event - Araya, Kunio (Himalayan Journal of Sciences, 2008)
Himalayan Journal of Sciences Vol.2(4) Special Issue 2004 pp. 96-97